UPAYA PAKSA PENANGKAPAN DAN PENETAPAN STATUS TERSANGKA TERHADAP TINDAK PIDANA PENCURIAN - Tantio Prabowo; Asep Iwan Iriawan (Fakultas Hukum Universitas Trisakti, 2022)
Although the Pretrial Institution was created as a mechanism of supervision to monitor the legality of investigators' use of their authority, in the reality, investigators continue to exercise their power arbitrarily without regard for the applicable processes and rules. The issue is whether the Gorontalo City Police Resort's arrest of Fadlan Ishak and determination of his status as a suspect was in accordance with Law Number 8 of 1981 regarding the Criminal Procedure Code and Perkap Number 6 of 2019, as well as whether the judge's decision to deny all of the applicant's requests in the Pretrial Court decision Gorontalo State Number 9/Pid.Pra/2020/PN.Gto conforms with the requirements of Perkap Number 6 of 2019 and Law Number 8 of 1981 regarding the Criminal Procedure Code. The research approach uses normative law, with qualitative data management and deductive conclusion-drawing. According to the findings of the investigation, the Gorontalo City Police Resort's forced arrest and determination of the suspect's status was in violation of Article 17, Article 18 paragraph (1), and Article 18 paragraph (2) of the Criminal Procedure Code because it was not supported by an assignment letter or an arrest warrant and was not based on enough preliminary evidence.